New Mechanisms of Biological Tissue Injury Following the Low Temperature Exposure In Vivo - Korpan, N. N. (Problems of Cryobiology and Cryomedicine, 2008)
A number of theoretical and experimental studies, both in vitro and in vivo, have been performed to explain the action of low temperatures on tissue. It is now evident that the thermal parameters used in the past for freezing during cryosurgery were not precise; this may have resulted in the failure of treatment. For the first time, this report describes the early ultrastructural features of pancreatic parenchyma after low temperature exposure, i.e. cryosurgery, in vivo. 48 animals were used for the experiment. A temperature range of –80°C and –180°C in contact with pancreas tissue was selected for cryosurgical exposure. The cryosurgical response of pancreas parenchyma, i.e. ultrastructural cellular changes in pancreas tissue, was investigated. For transmission electron microscopy, the specimens from the pancreas parenchyma were taken immediately, one hour and 24 hours after the finishing of the freeze-thaw cycles intraoperatively. The electronic microscopic analysis showed that, after local cryodestruction at temperatures of –80 and –180°C, similar processes occurred within the pancreas tissue in the early postcryosurgical phase – immediately and up to 24 hours after low temperature exposure on tissue. The exocrine pancreatic cells in the center of the cryozone changed upon thawing. Ultrastructural changes in the exocrine pancreatic cells, where the first signs of dystrophic processes had been noticed, were increased. These ultrastructural changes in the pancreatic cells provide a platform to better understand the mechanisms of damage and the pathogenesis of frostbite after cryosurgery. The properties of the pancreas parenchyma response after low temperature exposure provide important insights into the mechanisms of damage and the cryogenic lesion immediately after thawing in cryosurgery. Our new insights prove on the cell level that suddenly and progressively damaged pancreatic cells in the postcryosurgical zone lead to aseptic cryonecrosis and then to aseptic cryoapoptosis of vital normal tissue. The vascular capillary changes and circulatory stagnation demonstrate the antiangiogenesis mechanism, which, together with cryoaponecrosis and cryoapoptosis, are some of the main mechanisms of biological tissue injury following the low temperature exposure.